Clinical signs and clinical pathology findings in horses with equine encephalosis at the Onderstepoort Veterinary Academic Hospital, South Africa - Eberhardt, Christina (University of Pretoria, 2024)
Dissertation (MMedVet (Equine Medicine))--University of Pretoria, 2024.